The influence of social media marketing and celebrity endorsers on purchase intention with source credibility as a moderator variables - Herti Sitorus Br; Suryani Wan; Sabrina Hesti (Enrichment : Journal of Management, 2023)
This study aims to determine the influence of social media marketing and celebrity endorsers on purchase intention with source credibility as a moderator variable in Scarlett Whitening. This type of research is associative, that is, research to determine the relationship or influence between two or more variables using a linkert scale. The population of this study was Scarlett Whitening users with a sample of 170 respondents in the city of Medan, using the hair formula technique. Metode data analysis using SmartPLS 4, with descriptive analysis, Outer Model and Inner Model. The results of the study square of 0.692 on purchase intention so that it can be explained the influence of exogenous variables, namely social media marketing, celebrity endorsers simultaneously by 69.2% including strong and moderate. Based on the moderation test, Source credibility did not significantly moderate the influence of social media marketing on purchase intention with a moderation path coefficient of -0.080 with a statistical t value of 2,276 > 1.96 and P values of 0.131 > 0.05. Source credibility significantly moderates the influence of celebrity endorsers on purchase intention with a moderation path coefficient of 0.112 with a statistical t value of 1,120 > 1.96 and p values of 0.011 < 0.05.